Environmental Justice in OECD Environmental Performance Review: Chile 2016 - Costa Cordella, Ezio (Revista de Derecho Ambiental, 2017)
This paper works on the classification and explanation of different concepts of Environmental Justice, in order to make them more easy to pair with the public policy recommendations than the OECD gave to Chile in it Environmental Performance Review (2016). On one hand, this paper pretends to give more concrete destiny to Environmental Justice, by finding it as a part of the recommendations of a rather liberal organization, like OECD. On the other hand, integrating environmental justice into these advices, pretends to give them more sense and consistency. Lastly, with the analysis of the Performance Review, this paper reveals situations of environmental injustice related with reality and regulation in Chile.